The Maternal Adversity, Vulnerability and Neurodevelopment Project: Theory and Methodology. (September 2014) - O'Donnell, Katherine A; Gaudreau, Hélène; Colalillo, Sara; Steiner, Meir; Atkinson, Leslie; Moss, Ellen; Goldberg, Susan; Karama, Sherif; Matthews, Stephen G; Lydon, John E; Silveira, Patricia P; Wazana, Ashley D; et al.
Objective: To describe the theory and methodology of the multi-wave, prospective Maternal Adversity, Vulnerability and Neurodevelopment (MAVAN) study. The goal of MAVAN is to examine the pre- and postnatal influences, and their interaction, in determining individual differences in mental health. Method: MAVAN is a community-based, birth cohort study of pregnant Canadian mothers and their offspring. Dyads are assessed longitudinally, with multiple assessments of both mother and child in home and laboratory across the child's development. Study measures, including assessments of cognitive and emotional function, are described. The study uses a candidate gene approach to examine gene–environment interdependence in specific developmental outcomes. Finally, the study includes measures of both brain-based phenotypes and metabolism to explore comorbidities associated with child obesity. One of the unique features of the MAVAN protocol is the extensive measures of the mother–child interaction. The relation between these measures will be discussed. Results: Evidence from the MAVAN project shows interesting results about maternal care, families, and child outcomes. In our review, preliminary analyses showing the correlations between measures of maternal care are reported. As predicted, early evidence suggests that maternal care measures are positively correlated, over time. Conclusions: This review provides evidence for the feasibility and value of laboratory-based measures embedded within a longitudinal birth cohort study. Though retention of the samples has been a challenge of MAVAN, they are within a comparable range to other studies of this nature. Indeed, the trade-off of somewhat greater participant burden has allowed for a rich database. The results yielded from the MAVAN project will not only describe typical development but also possible targets for intervention. Understanding certain endophenotypes will shed light on the pathogenesis of various mental and physical disorders, as well as their interrelation.